The Correlation Between Students’ Vocabulary Mastery and Metacoginitive Reading Strategies on Students’ Critical Reading Ability - Nora, Wiwit Engrina; Utari, Zeli; Rahmayuni, Sisri; Arifmiboy, Arifmiboy (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigated how Vocabulary Mastery (VM) and Metacognitive Reading Strategies (MRS) worked together to shape students’ Critical Reading Ability (CRA) in an EFL setting—a relationship that had rarely been examined in combination. Critical reading was widely acknowledged as essential for academic success, yet many learners still faced difficulties due to limited lexical knowledge and the lack of strategic awareness needed to manage their reading processes. Using a quantitative correlational design, data were obtained from 30 ninth-grade students through a vocabulary test, the MARSI questionnaire, and a critical reading test. All instruments had undergone expert validation, pilot testing, and reliability checks. The descriptive findings showed that students demonstrated moderate levels of vocabulary mastery, metacognitive strategy use, and critical reading skills. Correlation analysis revealed strong positive relationships among the variables, with MRS showing the strongest association with CRA (r = 0.89). Regression results indicated that the overall model significantly predicted critical reading performance (R² = 0.811, p 0.001). While vocabulary mastery contributed to understanding, it did not remain a significant predictor when paired with metacognitive strategies. These findings suggested that strategic self-regulation played a more crucial role in enabling learners to interpret, evaluate, and respond critically to texts.